Safety of the current drug treatments for vitiligo. Issue 4 (2nd April 2020) - Lotti, Torello; Agarwal, Komal; Podder, Indrashis; Satolli, Francesca; Kassir, Martin; Schwartz, Robert A; Wollina, Uwe; Grabbe, Stephan; Navarini, Alexander A; Mueller, Simon M; Goldust, Mohamad
ABSTRACT: Introduction : Vitiligo is an acquired depigmenting skin disorder adversely affecting the patient's quality of life. Despite the presence of several treatment modalities, ranging from medical to physical to surgical options, none is curative. Each modality has its own drawbacks and side effects. Thus, the treatment modality needs to be tailored for each individual patient taking into consideration the disease characteristics and also its efficacy and safety to obtain a favorable risk–benefit ratio. Areas covered : This review highlights the different treatment modalities utilized in vitiligo up until 4 November 2019 along with their adverse effects and contraindications, if any. Expert opinion : All the medications have their own adverse effects and contraindications. We have included the most commonly used topical corticosteroids, which may result in striae, cutaneous atrophy, and tachyphylaxis, to the recently introduced biologics, which may induce hypersensitivity reactions, systemic toxicities, and even malignancies. However, more long-term studies are needed to assess the safety of these medications, especially the newer ones, to provide a safe and effective treatment for this disorder.